The Role of Serum Lipids in Predicting Suicidal Ideation in Isotretinoin Therapy for Acne - Gurok, Nese Gocer; Demir, Betul; Atmaca, Murad (Aves, 2024)
Background: Previous studies have demonstrated that lipids could play a role in suicidal ideation and the pathogenesis of psychiatric diseases. The present study aims to investigate the correlation between variations in serum lipid concentration, a side effect of isotretinoin (ITT), psychiatric symptoms, and suicidal ideation in acne vulgaris patients under ITT treatment. Methods: The study was completed with 41 acne patients. Patients were analyzed with the sociodemographic and clinical data form, Beck depression inventory (BDI), Beck anxiety inventory (BAI), Beck Suicidal Ideation Scale (BSS), and Brief Psychiatric Rating Scale (BPRS) at the beginning and on the third month of treatment. Lipid levels [serum total cholesterol (TC), triglyceride (TG) and high-density lipoprotein cholesterol (HDL)] were measured using the automatic chemistry analyzer (Beckman AU-5800). Serum low-density lipoprotein cholesterol (LDL) values were estimated with the Friedewald formula. Results: A statistically significant correlation was determined between the BSS scores and TC, TG, and LDL parameters at the beginning of treatment and the control date. Thus, it was determined that there was a negative weak correlation between BSS and TC parameters (r=-0.403; P= .009), a moderate negative correlation between BSS and TG (r=-0.526; P< .001), and a weak negative correlation between BSS and LDL (r=-0.421; P= .006). Furthermore, there were statistically significant changes between the BDI and BAI scores at the beginning of treatment and the third month (P= 0.016 and P= .001, respectively). Although an increase was observed in BSS and BPRS after the treatment compared to pretreatment, the increase was not statistically significant. Conclusion: The present study findings revealed that serum lipid levels could be associated with psychiatric side effects in patients under ITT treatment. But, this must not be the only way to detect the risk when we consider that serum lipid levels that have been associated with suicidal ideation, depression, and several psychiatric diseases have the potential to be an important indicator. In this context, our preliminary results open the doors to a new perspective in this regard, using the concept of blood lipid optimization. These findings need to be considered preliminary and supported by large sample
Keywords: Depressive Symptoms; Cholesterol Values; Retinoic Acid; Anxiety; Profile; Metaanalysis; Association; Disorders; Leptin; Risk